TANGGUNG GUGAT KREDITUR DAN PEJABAT LELANG ATAS PENENTUAN HARGA LIMIT LELANG DIBAWAH NILAI TANGGUNGAN - Yusuf, Muhammad (JURNAL MEDIA HUKUM DAN PERADILAN, 2019)
Main research material for Liability of Creditors and Upper Auction Officers Determination of Auction Limit Prices Under Depreciation Value, with the formulation of the problem What is the legal effect of auctioning objects whose auction limit is below the dependency and whether creditors and auction officials are accountable for auction limit pricing below the value of dependents. The conclusions are as follows: The act of creditor in determining the price of the auction limit below the value of the liability has fulfilled the whole element of article 1365 of the Civil Code so The legal consequence of auction object sales is that the auction price is below the value of the hold and if the object of the right of sale is sold under the value of the mortgage, the auction can be requested by the court. The creditor is liable for the price of the auction limit below the value of the creditor because the creditor as the seller does have the right to set the auction limit price but still must pay attention to the appropriateness of the specified auction limit price and the Auction Officer is not liable for the auction limit price below the hold value because the Auction Guidelines state that the auction limit price is not the responsibility of the KPKNL or the Class II Auction Officer